Optimisation of bioethanol production from oil palm trunk sap - Gimbun, Jolius; Nor Shahirah, Mohd Nasir; Sumaiya, Zainal Abidin; Cheng, Chin Kui; Maizirwan, Mel (EDP Sciences, 2023)
This paper presents an optimization of bioethanol production from oil palm trunk sap (OPTS) fermentation. The OPTS was obtained from an old palm tree (30 years old), whereas ethanol fermentation was carried out using Saccharomyces cerevisiae. The sugar content in OPTS and fermentation mother liquor was determined using high-performance liquid chromatography (HPLC). The parameters such as initial pH, temperature, and agitation rate were optimised using response surface methodology (RSM) with rotatable central composite design (CCD). It was found that the highest yield of bioethanol (75.82%) was obtained at the initial pH (5.79), temperature (31.05 °C), and agitation rate (164.38 rpm). The optimization model of OPTS fermentation to bioethanol developed in this work may provide useful guidance to obtain a high ethanol yield from OPTS.